Past and Present of the Comparative Studies on Latin American Cinema - Lusnich, Ana Laura (Universidad de Chile. Instituto de la Comunicación e Imagen, 2011)
This paper proposes a historical understanding of the theoretical and methodological lines that have characterized the studies about the Latin American cinema.  With its early exponents in the '80s and an increasing emphasis later, this trend consolidates a number of distinctive patterns, which were enriched by the work done by Latin American researchers, and a group of scholars that in other academic centers put their interest in our cinema. Based on a frame of reference the academic work with the most widely circulated at the international level, this paper focus on the recognition of the different phases that mark the history of comparative studies of Latin American cinema. Moreover, this work analyzes  the  comparative patters that organize the texts.